Reallocation and productivity during the Great Recession: Evidence from French manufacturing firms - Giacomo Domini; Daniele Moschella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
According to the "cleansing hypothesis", recessions are periods in which productivity-enhancing reallocation intensifies, shifting resources away from less efficient to more efficient firms at a greater pace. Does the Great Recession of 2008-2010 fit this view? We address this question, studying the case of the French manufacturing sector. Based on a panel of firms, built by matching data from several sources, we investigate the contribution of productivity to firm growth and survival over the period 2002-2013. Our results show that, during the recent global crisis, more productive firms decreased their advantage with respect to less productive firms, in terms of both employment growth and probability to survive, in disagreement with the cleansing hypothesis
Keywords: D22; D24; L20; L25; 330; firm productivity; selection; employment growth; global crisis